Thermal Resistance of Epoxy Resin and Phenol Formaldehyde Compound Mixed with Mixed Inhibitors - Mustafa A. Rajab (Journal of Global Pharma Technology, 2020)
The properties of flammability and the effect of zinc oxide with antimony trioxide were examined on the thermal corrosion testing of epoxy resin and formaldehyde. Zinc borate was added to the resin and then reinforced with silica fiber and woven glass fibers (90 ° -0º) with thickness (4 mm). Then expose the system to Acetylene Oxide flame (3500 ° C) directly with different exposures of flame (10 mm, 20 mm), to study flame retardant resistance and protection of the substrate. Animein trioxide was then added to zinc porcine in different quantities (10%, 20% and 30%) to form hybrid flame retardants for hybrid exposure to the same flame temperature and exposure distances. The method of measuring the surface temperature of the flame was used to determine the temperature transferred to the composite material. The results showed that the best exposed distance and a large proportion of protective layer of zinc boron with antimony trioxide was at 30%. Keywords: Hybrid Flame Retardants, Composite Material, Inorganic Retardants.